Alkaline batteries
By adding aromatic carboxylic acid and tin powder to the negative electrode, the alkaline dry battery addresses hydrogen generation and electrolyte leakage issues during misuse, ensuring battery safety and functionality.
Patent Information
- Application Number
- JP2022508054
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-18
- Filing Date
- 2020-12-08
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2040-12-08
AI Technical Summary
Existing alkaline dry batteries face issues with hydrogen generation and electrolyte leakage when misused by charging, leading to increased internal pressure and equipment malfunction, which existing technologies have not adequately addressed.
Incorporating an additive of aromatic carboxylic acid and tin powder into the negative electrode active material of alkaline dry batteries to maintain the negative electrode potential, suppress hydrogen generation, and prevent electrolyte leakage by accelerating the cycle of zinc corrosion, dissolution, and redeposition.
Effectively suppresses hydrogen generation and electrolyte leakage during misuse, maintaining battery integrity and preventing equipment malfunction.
Smart Images

Figure 0007607235000004 
Figure 0007607235000001 
Figure 0007607235000002
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an improvement in the negative electrode of an alkaline dry battery. [Background technology]
[0002] Alkaline dry batteries (alkaline manganese dry batteries) are widely used because they have a larger capacity and can extract a larger current than manganese dry batteries. An alkaline dry battery includes a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and an alkaline electrolyte contained in the positive electrode, the negative electrode, and the separator. The negative electrode includes a negative electrode active material containing zinc.
[0003] When using multiple alkaline batteries in series, one of the batteries may be mistakenly connected with the polarity reversed and charged. In addition, a primary alkaline battery may be mistakenly placed in a charger for secondary batteries and charged.
[0004] When an alkaline battery is misused and charged, hydrogen is generated inside the battery, causing the battery's internal pressure to rise. When the amount of hydrogen generated increases and the battery's internal pressure reaches a certain value, the safety valve operates and the hydrogen inside the battery is released to the outside. At this time, the alkaline electrolyte leaks out along with the hydrogen release, and the leaked alkaline electrolyte may cause equipment failure.
[0005] Patent Document 1 proposes an AA alkaline battery that uses zinc as the main active material of the negative electrode, manganese dioxide or nickel oxyhydroxide as the main active material of the positive electrode, a separator made of nonwoven fabric, and an aqueous potassium hydroxide solution as the electrolyte, and that is characterized in that 0.08 g to 0.1 g of zinc oxide is added to the battery.
[0006] Patent Document 2 proposes an alkaline dry battery comprising a positive electrode, a negative electrode, a separator, and at least an alkaline electrolyte held in the separator, in which the negative electrode contains zinc alloy powder as a negative electrode active material, and a gelled alkaline electrolyte, the gelled alkaline electrolyte containing 0.00002M parts by weight or more of a quaternary ammonium salt per 100 parts by weight of the zinc alloy powder (M is the molecular weight of the quaternary ammonium salt), and the alkaline electrolyte and the alkaline electrolyte in the gelled alkaline electrolyte each contain 0.3 mol / l or more of a zinc compound.
[0007] Patent Document 3 discloses an alkaline dry battery comprising a positive electrode containing manganese dioxide, a negative electrode containing zinc, a separator disposed between the positive electrode and the negative electrode, and an alkaline electrolyte, the air permeability of the separator being 0.5 to 5.0 ml / sec / cm 2 The manganese dioxide has a potential of 270 to 330 mV (vs. Hg / HgO), and the alkaline electrolyte contains 2.0 to 4.5% by weight of zinc oxide.
[0008] Patent Document 4 proposes an alkaline battery that uses a caustic alkaline aqueous solution as an electrolyte, and is characterized in that at least one compound selected from aryl carboxylic acids, their substituted derivatives, and their salts is added as a corrosion inhibitor for the negative electrode active material.
[0009] Patent Document 5 proposes an alkaline dry battery comprising a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte solution contained in the positive electrode, the negative electrode, and the separator, the electrolyte solution containing an alkaline aqueous solution, the negative electrode containing a negative electrode active material containing zinc, and an additive, the additive containing at least one selected from the group consisting of benzoic acid, phthalic acid, isophthalic acid, and salts thereof, the amount of the negative electrode active material contained in the negative electrode being 176 to 221 parts by mass per 100 parts by mass of water contained in the electrolyte, and the amount of the additive contained in the negative electrode being 0.1 to 1.0 part by mass per 100 parts by mass of the negative electrode active material.
[0010] Patent Document 6 proposes a zinc alkaline primary battery having a zinc negative electrode mainly made of corrosion-resistant zinc alloy powder that is mercury-free or mercury-free, and mixed with a granular, fibrous or flaky conductive material, at least the surface of which is alkali-resistant, easily mercury-resistant, and made of a metal or alloy more noble than zinc.
[0011] US Patent No. 5,399,633 proposes an electrochemical cell comprising an anode containing zinc, an aqueous alkaline electrolyte, a separator, and a cathode containing manganese dioxide, the anode further comprising a conductive metal powder physically mixed with the zinc.
[0012] Patent Document 8 proposes a gelled negative electrode for an alkaline electrochemical cell, the negative electrode comprising zinc-based particles, an alkaline electrolyte, a gelling agent, and two or more additives selected from the group consisting of alkali metal hydroxides, organophosphate ester surfactants, metal oxides, and tin. [Prior art documents] [Patent documents]
[0013] [Patent Document 1] JP 2006-156158 A [Patent Document 2] JP 2011-216218 A [Patent Document 3] International Publication No. 2010 / 140295 [Patent Document 4] Japanese Patent Publication No. 61-208753 [Patent Document 5] International Publication No. 2018 / 163485 [Patent Document 6] Japanese Patent Application Publication No. 61-96665 [Patent Document 7] Special Publication No. 2003-502808 [Patent Document 8] Special Publication No. 2018-514932 Summary of the Invention
[0014] When an alkaline dry battery is misused and continues to be charged, zinc precipitation due to reduction of zinc ions in the electrolyte at the negative electrode progresses, and the zinc ions in the electrolyte decrease. When the zinc ions in the electrolyte decrease, resistance to the zinc precipitation reaction increases significantly, the negative electrode potential drops rapidly, and the hydrogen generation potential is reached early. As a result, the amount of hydrogen generation increases, and the alkaline electrolyte leaks to the outside together with the release of hydrogen to the outside due to the operation of the safety valve. It is difficult to adequately deal with this problem with the proposals in Patent Documents 1 to 3. On the other hand, Patent Documents 4 to 8 do not provide any means for dealing with the problems caused by misuse of the battery.
[0015] One aspect of the present disclosure relates to an alkaline dry battery including a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and an alkaline electrolyte contained in the positive electrode, the negative electrode, and the separator, wherein the negative electrode includes a negative electrode active material containing zinc and an additive, and the additive includes an aromatic carboxylic acid and tin powder.
[0016] According to the present disclosure, when an alkaline dry battery is misused and charged, leakage of alkaline electrolyte to the outside of the battery can be suppressed. [Brief description of the drawings]
[0017] [Figure 1] FIG. 1 is a partially sectional front view of an alkaline dry battery according to an embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] An alkaline dry battery according to an embodiment of the present disclosure includes a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and an alkaline electrolyte (hereinafter simply referred to as electrolyte) contained in the positive electrode, the negative electrode, and the separator.
[0019] The negative electrode includes a negative electrode active material including zinc, and an additive, the additive including an aromatic carboxylic acid and tin (Sn) powder.
[0020] When an alkaline battery is misused and charged, zinc ions (Zn 2+ ) is reduced, causing a reaction in which zinc precipitates on the surface of the negative electrode active material. Therefore, the negative electrode potential is maintained at approximately -1.4 V (vs. Hg / HgO), which is the reduction potential of zinc ions. As charging of the alkaline dry cell continues, the zinc ions in the electrolyte decrease, increasing resistance to the above zinc precipitation reaction, and the negative electrode potential drops to below -1.7 V (vs. Hg / HgO), which is the decomposition potential of water in the electrolyte (hydrogen generation potential). The zinc ions in the electrolyte are zinc complex ions: Zn(OH)4 2- It exists as.
[0021] On the other hand, by incorporating the above-mentioned additive into the negative electrode, the cycle of zinc corrosion (formation of ZnO) on the surface of the negative electrode active material, dissolution of ZnO, and reprecipitation of zinc is accelerated, and the negative electrode potential is maintained near the reduction potential of zinc ions, thereby suppressing hydrogen generation and making it less likely that the safety valve will be activated due to an increase in internal pressure.
[0022] Although the mechanism by which the cycle of ZnO formation, dissolution, and re-precipitation of zinc accelerates is unclear, it is speculated that tin powder changes the precipitation form of zinc caused by charging due to misuse, and increases the specific surface area of zinc. The volume resistivities of Zn and Sn are 5.5 μΩcm and 11.5 μΩcm, respectively. Since Sn has a higher volume resistivity than Zn, precipitation of Zn occurs preferentially on the Zn surface. When tin powder is mixed with anode active material powder containing zinc, the tin powder close to the anode active material shields part of the surface of the anode active material powder. Zinc ions are precipitated by bypassing the surface shielded by the tin powder, which makes it easier for Zn to grow in a dendrite shape. This increases the specific surface area of zinc.
[0023] As the specific surface area of the precipitated zinc increases, the reactivity between the water in the electrolyte and zinc increases, and a relatively large amount of ZnO is produced on the zinc surface with a large specific surface area. ZnO dissolves in the electrolyte. Aromatic carboxylic acids form complexes with zinc ions in the electrolyte, promoting the dissolution of ZnO. The zinc ions released into the electrolyte by the dissolution of ZnO are redeposited on the surface of the negative electrode active material when the battery is charged due to misuse. This cycle continues, and the negative electrode potential is maintained near the reduction potential of zinc, suppressing hydrogen generation due to a decrease in the negative electrode potential.
[0024] Here, aromatic carboxylic acid is a general term for a compound having an aromatic ring and a carboxyl group directly bonded to the aromatic ring. The aromatic carboxylic acid may have at least one carboxyl group, but an aromatic polycarboxylic acid having two or more carboxyl groups is preferable because it is easy to form a stable complex with zinc ions in the electrolyte, and aromatic dicarboxylic acids are preferable. At least one carboxyl group of the aromatic carboxylic acid may form a salt. That is, the aromatic carboxylic acid may be an aromatic carboxylate. Examples of the cation substituted for H of the COOH group include an alkali metal ion, an ion of a group 2 element, an onium cation, and an ammonium ion. Examples of the alkali metal include sodium and potassium. Examples of the group 2 element include magnesium and calcium. The aromatic carboxylic acid may be ionized in the electrolyte and exist as an anion.
[0025] The aromatic ring may be a benzene ring, a naphthalene ring, or other rings, but is preferably a benzene ring. The aromatic ring may have a substituent that does not significantly inhibit the formation of a complex with zinc ions. Examples of aromatic dicarboxylic acids include benzene dicarboxylic acid (i.e., phthalic acids) and derivatives of benzene dicarboxylic acid. The derivatives include compounds having a substituent (e.g., methyl group, etc.) other than a carboxyl group bonded to a benzene ring, but do not include esters. Among phthalic acids, terephthalic acid is particularly preferred because it has a large effect of promoting the dissolution of ZnO. It is desirable that 90% by mass or more of the aromatic carboxylic acid is an aromatic dicarboxylic acid, it is desirable that 90% by mass or more of the aromatic dicarboxylic acid is a phthalic acid, and it is desirable that 90% by mass or more of the phthalic acid is terephthalic acid.
[0026] The amount of aromatic carboxylic acid (preferably aromatic dicarboxylic acid (more preferably terephthalic acid)) contained in the negative electrode may be, for example, 0.05 parts by mass or more and 0.5 parts by mass or less, 0.05 parts by mass or more and 0.3 parts by mass or less, or 0.08 parts by mass or more and 0.2 parts by mass or less per 100 parts by mass of the negative electrode active material. In this range, the effect of suppressing hydrogen generation during charging due to misuse is sufficiently large. In addition, better discharge performance can be obtained. The aromatic carboxylic acid may be added in advance to the electrolyte used to prepare the negative electrode. The concentration of the aromatic carboxylic acid in the electrolyte may be, for example, 0.05% by mass or more and 0.5% by mass or less.
[0027] Tin powder is suitable as an additive because it has a large hydrogen generation overvoltage and a specific gravity close to that of zinc, so that it is easily dispersed uniformly in the negative electrode active material and does not adversely affect the discharge reaction of the battery. The tin powder may be a powder containing metallic tin as a main component. The tin powder may be a tin alloy containing a trace amount of other elements, or may contain a trace amount of tin oxide. The tin powder may be a powder containing, for example, 20 mass% or less of elements other than tin, with the remainder being metallic tin.
[0028] In addition, when a zinc alloy is used as the negative electrode active material, the zinc alloy may contain tin. However, the tin contained in the negative electrode active material as a component of the zinc alloy has almost no effect of physically shielding a part of the surface of the negative electrode active material, and the effect of increasing the specific surface area of zinc cannot be expected. The tin powder is a powder separate from the negative electrode active material, and it is required that the particles of the negative electrode active material and the tin powder are mixed together.
[0029] As the negative electrode active material, zinc powder, zinc alloy powder, etc. are used. From the viewpoint of corrosion resistance, the zinc alloy may contain at least one selected from the group consisting of indium, bismuth, and aluminum. The indium content in the zinc alloy is, for example, 0.01 to 0.1 mass%. The bismuth content in the zinc alloy is, for example, 0.003 to 0.02 mass%. The aluminum content in the zinc alloy is, for example, 0.001 to 0.03 mass%. From the viewpoint of corrosion resistance, the ratio of elements other than zinc in the zinc alloy is preferably 0.025 to 0.08 mass%.
[0030] The negative electrode active material is usually used in the form of a powder. From the viewpoint of the packing property of the negative electrode and the diffusibility of the electrolyte in the negative electrode, the average particle size (D50) of the negative electrode active material powder is, for example, 100 to 200 μm, preferably 110 to 160 μm. In this specification, the average particle size (D50) is the median diameter in the particle size distribution based on volume. The average particle size is determined, for example, by using a laser diffraction / scattering type particle distribution measuring device.
[0031] The average particle size (D50) of the tin powder, which is an additive, is desirably smaller than that of the negative electrode active material powder, and may be, for example, 0.1 to 100 μm, or may be 0.1 to 10 μm. However, the average particle size D50s of the tin powder should not be excessively larger than the average particle size D50z of the negative electrode active material powder. For example, it is sufficient that the range satisfies D50s / D50z<1, and may also satisfy D50s / D50z<0.1.
[0032] The amount of tin powder contained in the negative electrode may be, for example, 0.05 parts by mass or more and 1 part by mass or less, 0.1 parts by mass or more and 0.5 parts by mass or less, or 0.2 parts by mass or more and 0.4 parts by mass or less per 100 parts by mass of the negative electrode active material. Within this range, the effect on the negative electrode capacity is negligibly small, and the effect of suppressing hydrogen generation during charging due to misuse is also sufficiently large.
[0033] The ratio (Mac / Ms) of the mass (Mac) of the aromatic carboxylic acid (preferably phthalic acid) to the mass (Ms) of the tin powder contained in the negative electrode is, for example, 0.05 to 1.05 in order to appropriately control the synergistic effect between the aromatic carboxylic acid and the tin powder. <Mac / Ms<10としてもよく、0.05<Mac / Ms<3としてもよい。
[0034] The positive electrode may contain the additives described above. Most of the additives added to the negative electrode remain in the negative electrode, but a small portion of the additives contained in the electrolyte in the negative electrode may migrate to the electrolyte in the positive electrode.
[0035] The alkaline dry battery according to an embodiment of the present disclosure may be a cylindrical battery, a coin battery, or the like.
[0036] The alkaline dry battery according to the present embodiment will be described in detail below with reference to the drawings. Note that the present invention is not limited to the following embodiment. In addition, appropriate modifications are possible within the scope of the effects of the present invention. Furthermore, the present embodiment can be combined with other embodiments.
[0037] Fig. 1 is a front view of an alkaline dry battery according to an embodiment of the present disclosure, with the horizontal half of the battery in cross section. Fig. 1 shows an example of a cylindrical battery having an inside-out structure. As shown in Fig. 1, the alkaline dry battery includes a hollow cylindrical positive electrode 2, a gelled negative electrode 3 disposed in the hollow portion of the positive electrode 2, a separator 4 disposed between them, and an electrolyte, all of which are housed in a cylindrical battery case 1 with a bottom that also serves as a positive electrode terminal. An alkaline aqueous solution is used as the electrolyte.
[0038] The positive electrode 2 is disposed in contact with the inner wall of the battery case 1. The positive electrode 2 contains manganese dioxide and an electrolyte. A gelled negative electrode 3 is filled in the hollow portion of the positive electrode 2 via a separator 4. The negative electrode 3 usually contains an electrolyte and a gelling agent in addition to a negative electrode active material containing zinc and the above-mentioned additives.
[0039] The separator 4 is cylindrical with a bottom and contains an electrolyte. The separator 4 is composed of a cylindrical separator 4a and a bottom paper 4b. The separator 4a is arranged along the inner surface of the hollow part of the positive electrode 2, and separates the positive electrode 2 from the negative electrode 3. Therefore, the separator arranged between the positive electrode and the negative electrode means the cylindrical separator 4a. The bottom paper 4b is arranged at the bottom of the hollow part of the positive electrode 2, and separates the negative electrode 3 from the battery case 1.
[0040] The opening of the battery case 1 is sealed by a sealing unit 9. The sealing unit 9 is composed of a gasket 5, a negative electrode terminal plate 7 that also serves as a negative electrode terminal, and a negative electrode current collector 6. The negative electrode current collector 6 is inserted into the negative electrode 3. The gasket 5 is provided with a safety valve having an annular thin-walled portion 5a. The negative electrode current collector 6 is nail-shaped with a head and a body, and the body is inserted into a through hole provided in the central cylindrical portion of the gasket 5, and the head of the negative electrode current collector 6 is welded to the flat portion in the center of the negative electrode terminal plate 7. The open end of the battery case 1 is crimped to the flange portion of the peripheral edge of the negative electrode terminal plate 7 via the outer peripheral end of the gasket 5. The outer surface of the battery case 1 is covered with an exterior label 8.
[0041] The alkaline dry battery will be described in detail below.
[0042] (Negative electrode) The negative electrode is obtained by mixing a negative electrode active material containing zinc (powder of zinc, zinc alloy, or the like), additives (aromatic dicarboxylic acid and tin powder), a gelling agent, and an electrolyte solution.
[0043] The gelling agent is not particularly limited, but may be, for example, a water-absorbent polymer, such as polyacrylic acid or sodium polyacrylate.
[0044] The amount of gelling agent contained in the negative electrode is, for example, 0.5 to 2.5 parts by mass per 100 parts by mass of the negative electrode active material.
[0045] A surfactant may be added to the negative electrode to adjust the viscosity. Examples of the surfactant include polyoxyalkylene group-containing compounds and phosphate esters, and among them, phosphate esters and their alkali metal salts are preferred. The surfactant may be added in advance to the electrolyte used to prepare the negative electrode.
[0046] (Negative electrode current collector) The material of the negative electrode current collector inserted into the gelled negative electrode may be, for example, a metal or an alloy. The negative electrode current collector preferably contains copper, and may be made of an alloy containing copper and zinc, such as brass. The negative electrode current collector may be plated with tin or the like, if necessary.
[0047] (positive electrode) The positive electrode usually contains manganese dioxide as a positive electrode active material, a conductive agent, and an electrolyte solution. The positive electrode may further contain a binder as necessary.
[0048] The manganese dioxide is preferably electrolytic manganese dioxide. The crystal structure of manganese dioxide may be α-type, β-type, γ-type, δ-type, ε-type, η-type, λ-type, or ramsdellite-type.
[0049] Manganese dioxide is used in the form of powder. From the viewpoint of easily ensuring the filling property of the positive electrode and the diffusibility of the electrolyte in the positive electrode, the average particle size (D50) of manganese dioxide is, for example, 25 to 60 μm.
[0050] From the viewpoint of moldability and suppression of expansion of the positive electrode, the BET specific surface area of manganese dioxide is, for example, 20 to 50 m 2 / g. The BET specific surface area is a surface area measured and calculated using the BET formula, which is a theoretical formula for multilayer adsorption. The BET specific surface area can be measured, for example, by using a specific surface area measuring device using a nitrogen adsorption method.
[0051] Examples of the conductive agent include carbon black such as acetylene black, and conductive carbon materials such as graphite. As the graphite, natural graphite, artificial graphite, etc. can be used. The conductive agent may be in a fibrous form, but is preferably in a powder form. The average particle size (D50) of the conductive agent is, for example, 3 to 20 μm.
[0052] The content of the conductive agent in the positive electrode is, for example, 3 to 10 parts by mass, preferably 5 to 9 parts by mass, relative to 100 parts by mass of manganese dioxide.
[0053] Silver or a silver compound such as Ag2O, AgO, Ag2O3, or AgNiO2 may be added to the positive electrode to absorb hydrogen generated inside the battery when the alkaline battery is charged due to misuse.
[0054] The positive electrode can be obtained, for example, by pressurizing a positive electrode mixture containing a positive electrode active material, a conductive agent, an alkaline electrolyte, and, if necessary, a binder into a pellet shape. The positive electrode mixture may be once formed into a flake or granule shape, classified if necessary, and then pressurized into a pellet shape.
[0055] After being housed in the battery case, the pellets may be subjected to a secondary pressure using a predetermined tool so as to adhere closely to the inner wall of the battery case.
[0056] (Separator) Examples of the material of the separator include cellulose and polyvinyl alcohol. The separator may be a nonwoven fabric mainly made of fibers of the above materials, or a microporous film such as cellophane or polyolefin. A nonwoven fabric and a microporous film may be used in combination. Examples of the nonwoven fabric include a nonwoven fabric mainly made of cellulose fibers and polyvinyl alcohol fibers, and a nonwoven fabric mainly made of rayon fibers and polyvinyl alcohol fibers.
[0057] In FIG. 1, a cylindrical separator 4 with a bottom is formed using a cylindrical separator 4a and a bottom paper 4b. The cylindrical separator with a bottom is not limited to this, and any separator with a known shape used in the field of alkaline dry batteries may be used. The separator may be formed of a single sheet, or, if the sheets constituting the separator are thin, multiple sheets may be stacked together. The cylindrical separator may be formed by rolling a thin sheet multiple times.
[0058] The thickness of the separator is, for example, 200 to 300 μm. The separator preferably has the above thickness as a whole, and if the sheets constituting the separator are thin, multiple sheets may be stacked to achieve the above thickness.
[0059] (electrolyte) The electrolyte is contained in the positive electrode, the negative electrode, and the separator. For example, an alkaline aqueous solution containing potassium hydroxide is used as the electrolyte. The concentration of potassium hydroxide in the electrolyte is preferably 20 to 50 mass %. The electrolyte may further contain zinc oxide. The concentration of zinc oxide in the electrolyte is, for example, 1 to 5 mass %.
[0060] The ratio (Mk / Ms) of the mass (Mk) of KOH contained in the alkaline dry battery (cell) to the mass (Ms) of tin powder contained in the negative electrode is set to, for example, 20 <Mk / Ms<580としてもよい。
[0061] (gasket) Examples of the material of the gasket include polyamide, polyethylene, polypropylene, etc. The gasket can be obtained, for example, by injection molding the above-mentioned material into a predetermined shape. The gasket usually has a thin-walled portion for explosion prevention. The thin-walled portion is preferably formed in a ring shape from the viewpoint of facilitating breaking. The gasket 5 in FIG. 1 has a ring-shaped thin-walled portion 5a. From the viewpoint of facilitating breaking of the thin-walled portion when the internal pressure increases, the gasket is preferably made of 6,10-nylon, 6,12-nylon, or polypropylene.
[0062] (Battery case) The battery case may be, for example, a cylindrical metal case with a bottom. The metal case may be, for example, a nickel-plated steel plate. In order to improve the adhesion between the positive electrode and the battery case, it is preferable to use a battery case in which the inner surface of the metal case is coated with a carbon film.
[0063] The present invention will be specifically described below based on examples and comparative examples, but the present invention is not limited to the following examples.
[0064] <Example 1> According to the following steps (1) to (3), a cylindrical AA alkaline battery (LR6) shown in FIG. 1 was fabricated.
[0065] (1) Preparation of the positive electrode A mixture was obtained by adding graphite powder (average particle size (D50) 8 μm) as a conductive agent to electrolytic manganese dioxide powder (average particle size (D50) 35 μm) as a positive electrode active material. The mass ratio of the electrolytic manganese dioxide powder to the graphite powder was 92.4:7.6. The electrolytic manganese dioxide powder had a specific surface area of 41 m 2 The mixture was mixed with the electrolyte and thoroughly stirred, and then compression-molded into flakes to obtain a positive electrode mixture. The mass ratio of the mixture to the electrolyte was 100:1.5.
[0066] The electrolyte used was an alkaline aqueous solution containing potassium hydroxide (concentration: 35% by mass) and zinc oxide (concentration: 2% by mass).
[0067] The flake-like positive electrode mixture was pulverized into granules, which were then classified using a 10 to 100 mesh sieve to obtain 11 g of granules. The granules were then pressure-molded into a predetermined hollow cylindrical shape with an outer diameter of 13.65 mm to produce two positive electrode pellets.
[0068] (2) Preparation of the negative electrode A negative electrode active material, zinc alloy powder (average particle size (D50) 130 μm), tin powder (average particle size (D50) 1.5 μm), terephthalic acid, an electrolyte, and a gelling agent were mixed together to obtain a gelled negative electrode 3. The electrolyte used was the same as that used in the preparation of the positive electrode.
[0069] The zinc alloy used was a zinc alloy (ZnBiAlIn) containing 0.02 mass% indium, 0.01 mass% bismuth, and 0.005 mass% aluminum. The electrolyte used was the same as that used in the preparation of the positive electrode.
[0070] The gelling agent used was a mixture of cross-linked branched polyacrylic acid and highly cross-linked linear sodium polyacrylate.
[0071] The amount of tin powder was 0.25 parts by mass per 100 parts by mass of the negative electrode active material. The amount of terephthalic acid was 0.14 parts by mass per 100 parts by mass of the negative electrode active material. The mass ratio of the negative electrode active material, the electrolyte, and the gelling agent was 100:50:1.
[0072] (3) Assembly of alkaline batteries A battery case 1 was obtained by applying Bunny Height manufactured by Nippon Graphite Co., Ltd. to the inner surface of a bottomed cylindrical battery case (outer diameter 13.80 mm, cylindrical wall thickness 0.15 mm, height 50.3 mm) made of nickel-plated steel sheet to form a carbon coating with a thickness of about 10 μm. Two positive electrode pellets were inserted vertically into the battery case 1, and then pressure was applied to form a positive electrode 2 in a state of being in close contact with the inner wall of the battery case 1. A bottomed cylindrical separator 4 was placed inside the positive electrode 2, and then the above electrolyte was injected to impregnate the separator 4. This state was left for a predetermined time, and the electrolyte was allowed to permeate from the separator 4 to the positive electrode 2. Then, 6 g of a gelled negative electrode 3 was filled inside the separator 4.
[0073] The ratio (Mk / Ms) of the mass (Mk) of KOH contained in the alkaline dry battery (cell) to the mass (Ms) of tin powder contained in the negative electrode was set to 114.
[0074] The separator 4 was composed of a cylindrical separator 4a and a bottom paper 4b. The cylindrical separator 4a and the bottom paper 4b were made of a nonwoven fabric sheet (basis weight 28 g / m2) mainly made of rayon fiber and polyvinyl alcohol fiber in a mass ratio of 1:1. 2 The thickness of the nonwoven fabric sheet used for the bottom paper 4b was 0.27 mm. The separator 4a was formed by rolling a nonwoven fabric sheet having a thickness of 0.09 mm three times.
[0075] The negative electrode current collector 6 was obtained by pressing a common brass (Cu content: about 65% by mass, Zn content: about 35% by mass) into a nail shape and then tin plating the surface. The diameter of the body of the negative electrode current collector 6 was 1.15 mm. The head of the negative electrode current collector 6 was electrically welded to a negative electrode terminal plate 7 made of nickel-plated steel plate. Then, the body of the negative electrode current collector 6 was pressed into the central through hole of a gasket 5 mainly composed of polyamide 6,12 and having a safety valve in a thin part. In this way, a sealing unit 9 consisting of the gasket 5, the negative electrode terminal plate 7, and the negative electrode current collector 6 was produced.
[0076] Next, the sealing unit 9 was placed in the opening of the battery case 1. At this time, the body of the negative electrode current collector 6 was inserted into the negative electrode 3. The open end of the battery case 1 was crimped to the peripheral edge of the negative electrode terminal plate 7 via a gasket 5, thereby sealing the opening of the battery case 1. The outer surface of the battery case 1 was covered with an exterior label 8. In this manner, an alkaline dry battery A1 was produced.
[0077] [evaluation] The following evaluation test was carried out using the battery A1 prepared above. One battery A1 was prepared and connected to a circuit that carried a reverse connection current of 0.1 A, and the presence or absence of leakage from the battery was checked 60 minutes after the start of reverse connection.
[0078] The above evaluation test was carried out five times, and the number of batteries that leaked (the number of leaks) was calculated.
[0079] The above evaluation test was conducted under the assumption that one battery was mistakenly connected with the polarity reversed when four batteries were connected in series to a low-load (30 Ω) device. The 60-minute charging time was set taking into consideration the time it would take a user to insert the batteries into the device, notice that the device is not functioning properly, check the battery installation, and remove the battery.
[0080] <Comparative Example 1> An alkaline dry battery B1 was produced and evaluated in the same manner as in Example 1, except that no tin powder was used as an additive in the production of the negative electrode.
[0081] <Comparative Example 2> An alkaline dry battery B2 was produced and evaluated in the same manner as in Example 1, except that terephthalic acid was not used as an additive in the production of the negative electrode.
[0082] <Comparative Example 3> An alkaline dry battery B3 was produced and evaluated in the same manner as in Example 1, except that in the preparation of the negative electrode, no tin powder was used as an additive, and a zinc alloy (ZnBiAlInSn) containing 0.02 mass % indium, 0.01 mass % bismuth, 0.005 mass % aluminum, and 0.01 mass % tin was used as the zinc alloy serving as the negative electrode active material.
[0083] <Comparative Example 4> An alkaline dry battery B4 was produced and evaluated in the same manner as in Example 1, except that in the preparation of the negative electrode, neither tin powder nor terephthalic acid was used as an additive.
[0084] The evaluation results are shown in Table 1.
[0085] [Table 1]
[0086] In the battery A1 of Example 1 in which terephthalic acid and tin powder were added to the negative electrode, the number of leakages was 0. On the other hand, in the batteries of Comparative Examples 1 to 4 in which at least one of terephthalic acid and tin powder was not used, leakage was observed in 80% or more of the batteries. In Comparative Example 3, a zinc alloy containing tin was used as the negative electrode active material, but the effect of using tin powder was not observed.
[0087] <Examples 2 to 5> Alkaline batteries A2 to A5 were produced and evaluated in the same manner as in Example 1, except that in the preparation of the negative electrode, the amount of tin powder per 100 parts by mass of the negative electrode active material was fixed at 0.25 parts by mass, and the amount of terephthalic acid per 100 parts by mass of the negative electrode active material was changed as shown in Table 2. The evaluation results are shown in Table 2.
[0088] [Table 2]
[0089] <Examples 6 to 9> Alkaline batteries A6 to A9 were produced and evaluated in the same manner as in Example 1, except that in the preparation of the negative electrode, the amount of terephthalic acid per 100 parts by mass of the negative electrode active material was fixed at 0.14 parts by mass, and the amount of tin powder per 100 parts by mass of the negative electrode active material was changed as shown in Table 3. The evaluation results are shown in Table 3.
[0090] [Table 3]
[0091] It can be seen from Tables 2 and 3 that leakage does not occur when the amount of tin powder contained in the negative electrode is controlled to 0.05 parts by mass or more and 1 part by mass or less per 100 parts by mass of the negative electrode active material, or when the amount of aromatic carboxylic acid contained in the negative electrode is controlled to 0.05 parts by mass or more and 0.5 parts by mass or less per 100 parts by mass of the negative electrode active material. From the above, it can be seen that hydrogen generation can be more effectively suppressed by using additives in the above ranges. [Industrial Applicability]
[0092] The embodiments of the present disclosure can be applied to any device (especially a low-load device) that uses a dry cell as a power source, such as a radio, a clock, or a portable music player. [Explanation of symbols]
[0093] 1 Battery case 2 Positive electrode 3 negative electrode 4. Cylindrical separator with bottom 4a Cylindrical separator 4b bottom paper 5 Gasket 5a Thin wall part 6 Negative electrode current collector 7 Negative terminal plate 8 Exterior Label 9. Sealing unit
Claims
1. A battery comprising: a positive electrode; a negative electrode; a separator disposed between the positive electrode and the negative electrode; and an alkaline electrolyte contained in the positive electrode, the negative electrode, and the separator; The negative electrode includes a negative electrode active material including zinc and an additive, The additive comprises an aromatic carboxylic acid and tin powder.
2. 2. The alkaline dry battery according to claim 1, wherein the amount of tin powder contained in the negative electrode is 0.05 parts by mass or more and 1 part by mass or less per 100 parts by mass of the negative electrode active material.
3. 3. The alkaline dry battery according to claim 1, wherein the amount of the aromatic carboxylic acid contained in the negative electrode is 0.05 parts by mass or more and 0.5 parts by mass or less per 100 parts by mass of the negative electrode active material.
4. The alkaline dry battery according to claim 1 , wherein the aromatic carboxylic acid includes an aromatic dicarboxylic acid.
5. The alkaline dry battery of claim 4 , wherein the aromatic dicarboxylic acid comprises phthalic acid.
6. 6. The alkaline dry battery of claim 5, wherein the phthalic acid comprises terephthalic acid.
Citation Information
Patent Citations
Zinc alkaline primary battery
JP1986096665A
Alkaline battery
JP1986208753A
Zinc powder for alkali cell and preparation thereof
JP1990194103A
Manganese dry battery
JP1990226657A
Alkaline battery with improved anode
JP2003502808A